Molecular and Cellular Studies of Human Hepatitis B Virus Variants - Ong, Hooi Tin (2004)
Despite unceasing efforts of the medical community, hepatitis B remains, besides hepatitis C, the most serious type of viral hepatitis and one of the major problems of global public health. According to the latest World Health Organization fact sheets (2000), of the 2 billion people who have been infected with the hepatitis B virus (HBV), more than 350 million have chronic infections. These chronically infected persons are at high risk of death from cirrhosis of the liver and liver cancer, diseases that kill about 1 million persons each year (WHO, 2000). The prevalence of HBV varies tremendously in different part of the world, with a much higher incidence in the Eastern than in the Western Hemisphere (WHO, 2001). High prevalence areas have been identified in Southeast Asia, China and Africa (reviewed by Lee, 1997). About 100 million carriers, making up 75% of the world’s HBV carriers living in Asia, are from China (Tandon and Tandon, 1997). In Malaysia, voluntary testing carried out on 17 048 healthy volunteers indicated a HBsAg seropositivity of 5.24% (Merican et al., 2000). xxv HBV belongs to the Orthohepadnavirus genus of the Hepadnaviridae family, which is related to the large order of Retroid viruses (Kann and Gerlich, 1998). Within a size of only about 3.2 kb, its compact, partially double-stranded DNA genome is extremely small, bearing four highly overlapping open reading frames (ORFs), which encode at least seven proteins (Kann and Gerlich, 1998; Nassal, 1999; Seeger and Mason, 2000). Due to the use of a viral RNA-dependent polymerase without proofreading function, HBV has a higher mutational rate than other DNA viruses (Blum1995; Petzold et al., 1999). Thus, it is generally assumed that this reverse transcription step accounts for the majority of point mutations and deletions or insertions that can be observed in the HBV genome. There are 2 major types of mutations in HBV. Firstly, there are genotype-specific mutations that allow the distinction of currently eight genotypes (A-H) (Norder et al., 1993; Stuyver et al., 2000; Arauz-Ruiz et al., 2002). These genotypes cluster geographically. Genotype A seems to represent the main European inland strain; genotype B and C, the Asian strain; genotype D, the Mediterranean basin strain; genotype E, the African strain; and genotype F, the New World strain (Norder et al., 1994; Magnius and Norder, 1995; Kidd Ljunggren, 1996). Genotype G was identified in France and United States (Stuyver et al., 2000) and genotype H was recently encountered in Nicaragua, Mexico and California (Arauz-Ruiz et al., 2002). xxvi The second type of HBV variability concerns mutations that emerge in an individual during chronic infection. Several specific mutations of this type have been identified by a large number of longitudinal as well as cross-sectional studies conducted during the past decade (reviewed in Gunther et al., 1999). Most of the corresponding variants accumulate during infection and persist as a dominant population until the late phase. These mutants are clinically important. It is learned that the presence or emergence of specific mutations is associated with particular stages of chronic infections (Gunther et al., 1999). In general, the enhancer II/core promoter and precore stop codon mutants appear to be associated with disease severity and progression (Lindh et al., 1999; Scaglioni et al., 1997; Pult et al., 1997; Takahashi et al., 1999). Mutations in the core antigen contribute strongly to immune escape at the T helper and cytotoxic T lymphocyte (CTL) level (Wakita et al., 1991; Chisari and Ferrari, 1995). Recent reports also revealed that mutations at basal core promoter (BCP) and precore/core (preC/C) mutations may influence the response rate to interferon-alpha (IFN-α) therapy (Fattovich et al., 1995; Zhang et al., 1996; Erhardt et al., 2000). Surface antigen mutants allow for escape from humoral immune responses and reduce the effectiveness of diagnostic tests and vaccination (Waters et al., 1992; Karthigesu et al., 1994; Carman et al., 1995,; Wallace and Carman, 1997; Hsu et al., 1999a). xxvii HBV is a typical non-cytopathic virus that can induce tissue damage of variable severity by stimulating a protective immune response that can simultaneously cause damage and protection, by resolving intracellular virus through the destruction of virus infected cells (Ferrari et al., 2003). Therefore, immune elimination of infected cells can lead to the termination of infection when it is efficient, or to a persistent necroinflammatory disease when it is not. Destruction of infected cells, however, is not the only mechanism implicated in the elimination of intracellular virus, as demonstrated by studies carried out in human hepatitis B showing the importance of cytokine-mediated, non-cytolytic mechanisms of antiviral protection. The first experimental evidence in favour of such mechanisms derives from studies performed in the transgenic mouse model (Guidotti and Ferrari, 2001). These studies showed that single stranded and relaxed circular double stranded HBV DNA replicative intermediates can be eliminated from the cytoplasm of HBV transgenic hepatocytes as a result of the antiviral effect of the interferon-gamma (IFN-γ) and tumour necrosis factor-alpha (TNF-α) released within the transgenic liver primarily by infiltrating HBV-specific CD8+ cells (Guidotti et al., 1996; Heise et al., 1999b) but also CD4+ T cells (Franco et al., 1997). Although the existence of genotypes is known for a long period of time, only very recently an association of genotype and clinical outcome was proposed (Kao et al., 2000a; Lindh et al., 1999). Recently, HBV genotypes have been partially clarified as xxviii influencing the clinical manifestation of chronic liver disease in hosts. A higher disease-inducing capability of genotype C than genotype B has been observed in Asia (Orito et al., 2001a; Kao et al., 2000a; Lindh et al., 1999). Several studies, mostly from Taiwan and Japan, have shown that HBV genotype C is associated with the development of hepatocellular carcinoma (HCC) (Kao et al., 2000a; Ding et al., 2001; Fujie et al., 2001) and has a lower response rate to interferon therapy as compared to genotype B (Kao et al., 2000b). As for other HBV genotypes, most patients in Europe with genotype A have chronic hepatitis, whereas most patients with genotype D have acute hepatitis (Mayerat et al., 1999) and may predict the occurrence of HCC in young Indian patients (Thakur et al., 2002). The genotype-related differences in HBV pathogenesis have been associated with the HBeAg/anti-HBe status. In the natural course of chronic HBV infection, early HBeAg/anti-HBe seroconversion usually associated with the cessation of virus replication and thus a favourable outcome (Chen, 1993). In contrast, late seroconversion of HBeAg after multiple episodes of reactivation and remission may accelerate the progression of chronic hepatitis B and thus have a poor clinical outcome (Perillo, 2001). Reports have revealed that the prevalence of HBeAg is more common in HBV genotype C than B. The reverse held true for the prevalence of anti-HBe, in that it is less common in genotype C than B (Ding et al., 2002; Chu et al., 2002; Kao et al., 2002; Orito et al., 2001a; Kobayashi et al., 2002; Yuen et al., 2003; Akuta et al., 2003). xxix Taken together, these data from different parts of the world have lent strong support to possible pathogenic differences among HBV variants. At present, those findings have been reported only in a few Asian countries. Moreover, the molecular virologic mechanisms that contribute to these clinical differences among HBV genotypes remain to be explored. The major limitation of previous studies is the lack of simple and efficient genotyping methods. Genotyping of viruses by sequencing and subsequent homology comparison or phylogenetic tree analysis is tedious and labour intensive and, therefore, not practical for diagnostic purposes. With the recent advances in molecular techniques, several novel genotyping methods, including polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) (Lindh et al., 1997; Mizokami et al., 1999), PCR with type-specific primers (Naito et al., 2001), commercial hybridization assay (Hou et al., 2001) and serologic genotyping assay (Usuda et al., 1999) have been introduced. In Malaysia, where the incidence rate of HBV was 12.19 per 100,000 population in 2001 (Ministry of Health Malaysia, 2001), limited information on the molecular biology of the HBV is available. The prevalence of HBV genotypes and the clinical relevance of HBV variants have not been discussed. The studies from other areas may not apply worldwide because the HBV strains in various parts of the world are different, and thus the clinical outcome and the mechanisms responsible may be different in this country. This provided a strong motivation to investigate the molecular variants of HBV in our population and the immune response evoked by these HBV variants.